Taxonomic revision of the Boiga ceylonensis group (Serpentes: Colubridae): re-examination of type specimens, redefinition of nominate taxa and an updated key - Ganesh, S.r.; Achyuthan, N.s.; Chandramouli, S.r.; Vogel, Gernot (Zootaxa, 2020)
We conducted a taxonomic revision of the arboreal snakes of the Boiga ceylonensis-group, all inhabiting the Indian subcontinent. Based on 15 characters, recorded from more than 100 specimens, representing eight recognized taxa, we conducted a multivariate morphometric analysis to redefine the taxonomic boundaries. We provide redescriptions of the nominate taxa in this group based on re-examination of the name-bearing types. The types of B. ceylonensis, B. beddomei, B. barnesii, B. dightoni, B. nuchalis and B. andamanensis are redescribed, where appropriate lectotypes are selected, illustrated and their nomenclature, synonymy and distribution are discussed. Status of the nominate taxon Boiga ceylonensis dakhunensis Deraniyagala, 1955 is fixed as an objective junior synonym of Dipsas nuchalis Günther, 1875. An updated key to the species of this group is presented.